Studies On Foraging And Evaluations Of Imidacloprid Treatments For Controlling Subterranean Termites In Selected Premises (Isoptera:Rhinotermitidae) [QL529. H139 2007 f rb]. - Ab Majid, Abdul Hafiz (2008)
A survey was conducted in Penang to determine the main termite infestation in buildings.